Hypomethylation of Sonic hedgehog in colorectal cancer (Bangladesh Journal of Medical Science, 2024)
Background: Past research has demonstrated that a changed Sonic Hedgehog (SHH) pattern contributes to the development of colorectal cancer. This study’s objective was to determine whether the SHH gene’s promoter hypomethylation might be used to predict the likelihood of developing colorectal cancer.Methods: For the current investigation, 50 newly diagnosed and untreated colorectal cancer patients’ tumor samples and surrounding non-tumor tissues were gathered. SHH methylation was determined by methylation-specific PCR (MSP) and results correlated with several studied clinicopathological parameters.Results: Our results showed that SHH methylation levels are significantly present in normal tissues as compared to tumor tissues.Conclusion: We conclude SHH promoter is hypomethylated in colorectal cancers which may have an effect driving normal colon and rectum cells to cancer.Bangladesh Journal of Medical Science Vol. 23 No. 01 January’24 Page : 200-206